Representasi Pola Komunikasi Keluarga dalam Film “Sabtu Bersama Bapak” - Sigit Surahman; Tiara Dewi Asmarani; Annisarizki Annisarizki; Eko Hari Saksono (Institut Seni Indonesia Yogyakarta, 2023)
The film Sabtu Bersama Bapak communication patterns between characters interacting with each other, the communication patterns presented can be verbal or non-verbal communication, this film illustrates that each family has different communication patterns depending on the situation and conditions. This research aims to describe the concept of communication patterns which divide four types of family communication, namely consensual, pluralistic, protective and laissez-faire communication patterns. Through a qualitative approach using Roland Barthes' semiotic analysis method to understand the meaning of denotation, connotation and myth. Data collection techniques use observation, documentation and interview techniques. The research results show that the film Sabtu Bersama Bapak represents the communication patterns of two families. In the Gunawan family there is a consensual communication pattern and a pluralistic communication pattern, while in the Satya family there is a consensual communication pattern and a protective communication pattern, and in this research no free communication pattern was found (laissez- faire).